Sistem Penjualan Berbasis Web menggunakan Metode Supply Chain Managemen untuk Manajemen Persediaan Barang - Lubis, Irgi Arianda; Maharani, Dewi; Dristyan, Febri (Universitas Hamzanwadi, 2024)
The manual inventory management at Andriani Wholesale Store in Air Teluk Kiri Village causes instability and significant fluctuations in stock levels. This problem leads to financial losses, high storage costs, and the loss of customers. This research aims to create a web-based sales system for inventory management integrated with the supply chain management (SCM) method. The model we use in building this system is the waterfall model, with stages of analysis, design, development or implementation, and testing. The testing we conducted used black box testing to ensure that the application or system could perform the desired functions according to the specified requirements. The data collection methods we used were interviews and observations. The data was processed using the SCM concept. Our findings resulted in a web-based sales system applying the SCM concept. The testing results showed that the system could perform its functions well without errors. With this system, real-time inventory monitoring, improved planning, and better communication with suppliers at Andriani Wholesale Store are achieved.